Análise dos algoritmos de perfil II do projeto eSTREAM para criptografia de imagens - Cerqueira César, João Paulo Fernandes de (2017)
Security and privacy have always been the subject of research. Nowadays with the popularization of the mass media, like the Internet, this subject becomes even more fundamental. Communication today is not only accomplished by exchanging text or audio files, but also by exchanging digital images. Encryption systems have been constantly enhanced and standardized to provide security and privacy, as well as algorithms for ciphering images. Although they are translated into binary data as well as texts, the images have particular characteristics that prevent the use of popular cryptographic systems, such as RSA and AES. The increasing use of cameras in computer systems, such as in autonomous cars and surveillance systems, fosters the need for techniques for secure image transmission. In addition, applications that work with real-time decision-making require low latency, making such hardware implementation desirable. Stream ciphers systems are compact and simple to implement, to promote their development ECRYPT (European Network of Excellence for Cryptology) has organized the eSTREAM project, resulting in a portfolio of validated stream ciphers for software and hardware implementations. The development of cryptographic systems in hardware is advantageous because of the high throughput provided by this paradigm, in addition, reconfigurable platforms such as Field Programmable Gate Arrays (FPGAs) offer flexibility and low cost in the development of new solutions. The present project aims at the implementation in FPGA of the cryptography systems of Profile II of the project eSTREAM and analysis of the quality of its figures when applied in the security of digital images.